Strategic planing of firm capital structure development - A. Kirshin, Igor (2018)
They modeled firm capital structure in the article within a strategic planning system focused on its value growth. Within the framework of strategic planning, the authors proposed the ways to quantify various financial indicators that form a firm value. The authors justify the thesis that when a firm value growth is planned, not only the valuation of capital is important, but also the development of a strategic financial model that ensures the achievement of a firm capitalization planned value. In order to approbate the proposed approach of a company value strategic planning, the structure of PJSC "Tatneft" capital was modeled according to the financial statements for the period from 2007 to 2016. Completed application developments allowed to supplement the theoretical model with a practical content. The obtained results indicate the maximum value of PJSC "Tatneft" achievement at the level of the borrowed funds in the range of 15-16% within the company capital structure. Based on the applied modeling results, the authors made the following conclusions. First, the decision to optimize the capital structure should be the part of the developed strategic planning system, which takes into account the company position in the market, perspective investments, expected free cash flow, and the distribution policy of net profit. Secondly, long-term firm management plans for credit resource attraction must be accompanied by financial difficulty risk assessments, the forecast of profit and the amount of free cash flow.